Assessing the Usefulness of Standing Flexion Test for Functional Diagnostics of the Sacroiliac Joints - Sebastian Szajkowski; Jarosław Pasek; Michał Dwornik; Tomasz Marcinkiewicz; Grzegorz Cieślar (Rehabilitacja Medyczna)
Introduction: Sacroiliac joint dysfunctions are common among patients visiting physiotherapy offices. The main symptom of these dysfunctions is pain in the lumbosacral region of the spine. Taking the frequency of its occurrence into account, it is important to conduct an appropriate diagnosis that enables the implementation of proper treatment.Material and methods: The study included 87 participants (70 women and 17 men) aged 24 to 74 years, on average: 58.93 10.98 years, with diagnosed blockage of the sacroiliac joints, both with pain symptoms and without pain in the sacroiliac joints area. In the study, palpation assessment regarding the position of the posterior superior iliac spines (PSIS), the anterior superior iliac spines (ASIS) and the iliac crests (IC) was performed in a standing position. The Standing Flexion test was used to assess mobility of the sacroiliac joints.Results: The symmetry of positioning in the PSIS, ASIS and IC static was found in 38 out of 87 subjects. Pain during the PSIS Standing Flexion test occurred in 43 (49.42%) people out of 87 subjects. The majority of respondents, i.e. 57 (65.52%), experienced pain in the area of the lumbar spine. The relationship between symmetry and asymmetry of PSIS movement with the pelvis set symmetrically or asymmetrically in the static was analysed. Statistically significant differences (p=0.015) concerned the occurrence of pain in the area of the lumbar spine. There were no statistically significant differences (p=0.218) in the incidence of pain during the PSIS Standing Flexion test. Pain was not more frequent when symmetric PSIS movement was observed in the study, despite asymmetric insertion of the iliac bones in static conditions. Conversely, pain was more often observed when there was no symmetrical PSIS movement.The results of examination regarding positioning of the hip bones in standing position are presented in Table 1.